Endornaviruses: persistent dsRNA viruses with symbiotic properties in diverse eukaryotes - Fukuhara, Toshiyuki (Virus genes, 2019)
Endornaviruses are unique, persistent, double-stranded RNA (dsRNA) viruses with symbiotic properties that infect diverse eukaryotes, such as plants, fungi, and oomycetes. Endornaviruses contain a linear dsRNA genome of approximately 10 to 17 kbp in length and are classified in the family Endornaviridae , which consists of two genera, Alphaendornavirus and Betaendornavirus . The endornaviruses encode a single long open reading frame encoding approximately 3200 to 5800 amino acid residues of conserved viral RNA helicase and RNA-dependent RNA polymerase domains, and some endornaviruses contain a site-specific nick in the coding strand of their dsRNA genome. Acute plant viruses propagate rapidly and systemically, eventually killing the host plant, and are then transmitted horizontally. In contrast, plant endornaviruses have several common persistent (symbiotic) properties: a stable low copy number in the host plant, no obvious effect on the host plant, and efficient vertical transmission via gametes. Plant endornaviruses are likely maintained within host plants for hundreds of generations, so the host must stringently regulate their propagation. Whereas RNA silencing functions as a defense system against acute viruses in plants, it may be necessary for the persistent infection (symbiotic life cycle) of endornaviruses. This process includes the stringent regulation of low virus copy number (steady replication before every host cell division) and efficient vertical transmission of the virus to the next generation.